Haptic-Based Perception-Empathy Biofeedback Enhances Postural Motor Learning During High-Cognitive Load Task in Healthy Older Adults - Yasuda, Kazuhiro; Saichi, Kenta; Iwata, Hiroyasu (Frontiers in Medicine, 2018)
Falls and fall-induced injuries are major global public health problems, and sensory input impairment in older adults results in significant limitations in feedback-type postural control. A haptic-based biofeedback (BF) system can be used for augmenting somatosensory input in older adults, and the application of this BF system can increase the objectivity of the feedback and encourage comparison with that provided by a trainer. Nevertheless, an optimal BF system that focuses on interpersonal feedback for balance training in older adults has not been proposed. Thus, we proposed a haptic-based perception-empathy BF system that provides information regarding the older adult’s center-of-foot pressure pattern to the trainee and trainer for refining the motor learning effect. The first objective of this study was to examine the effect of this balance training regimen in healthy older adults performing a postural learning task. Second, this study aimed to determine whether BF training required high cognitive load to clarify its practicability in real-life settings. Twenty older adults were assigned to two groups: BF and control groups. Participants in both groups tried balance training in the single-leg stance while performing a cognitive task (i.e., serial subtraction task). Retention was tested 24 h later. Testing comprised balance performance measures (i.e., 95% confidence ellipse area and mean velocity of sway) and dual-task performance (number of responses and correct answers). Measurements of postural control using a force plate revealed that the stability of the single-leg stance was significantly lower in the BF group than in the control group during the balance task. The BF group retained the improvement in the 95% confidence ellipse area 24 h after the retention test. Results of dual-task performance during the balance task were not different between the two groups. These results confirmed the potential benefit of the proposed balance training regimen in designing successful motor learning programs for preventing falls in older adults.